Rancang Bangun Sistem Monitoring Kualitas Air dengan menggunakan Arsitektur Jaringan Internet of Things - Ayub Firdhouzi; Primantara Hari Trisnawan; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Water is the essential compound for all living things on this earth. Human needs fresh water for their daily activities. Because of the importance of water use, the quality of water must be maintained. Make a water monitoring system can be one of the ways to maintain water quality. The monitoring system can be done by using the Internet of Things (IoT) technology. In the application, it will be constructed by three main component systems such as Producer, Broker, and Consumer. In building the IoT network architecture communication protocols are needed between the nodes to exchange data. The protocol that is used in this research is the Advanced Message Queueing Protocol (AMQP) and WebSocket. The AMQP was chosen because the network used in this research was considered capable of suiting the needs of the AMQP protocol. WebSocket protocol used for means of data communication so the results of monitoring can be shown on a web page in real-time. According to the result of tests conducted indicate that the system is capable of real-time monitoring, it's based on delay value in data transfer obtained. By using this water quality monitoring system, it is hoped that later it will be able to monitor the quality of water in real-time via the web.